Characterization and Animal Skin Irritations Investigation of Vemurafenib Microemulsion-Based Hydrogel Using Oily Ionic Liquid - J. Neamah, Mohammed; J. Al- Akkam, Entidhar (The Iraqi Journal of Veterinary Medicine, 2024)
Cutaneous melanoma accounts for a yearly mortality rate of 55,500 persons. The use of oral small-molecule kinase inhibitors, specifically targeting BRAFv600, has been licensed as the principal treatment strategy for managing both locally progressed and metastatic presentations of the condition. Approximately 30% of people on vemurafenib, a BRAFv600 inhibitor, have side effects when are taken orally. Objective: This research was attempted to develop a vemurafenib microemulsion by substituting conventional oil phases with ionic liquids (ILs). The microemulsions were created by dissolving vemurafenib in a combination of ionic liquid (1-Butyl-3-methylimidazolium hexafluorophosphate and 1-Octyl-3-methylimidazolium hexafluorophosphate) and surfactant (Triton x-100). Multiple tests were conducted to measure physical stability, pH determination, content homogeneity examination, and in vitro medicine release analysis. Four formulations of Vemurafenib microemulsions successfully met all criteria in the microemulsion characterisation and assessment tests. The droplet sizes in these microemulsions fell inside the range of microemulsions, which is less than 200 nm. They were then used to create microemulsion-based hydrogels, employing Carbamer 340 as a gelling agent by conducting a simple mixing method. Hydrogels formed from microemulsions containing 1-Octyl-3-methylimidazolium hexafluorophosphate demonstrated the ability to form clear hydrogels with desirable consistency. Regarding Ex-vivo permeability study and skin deposition the permeability profiles of GOT3 formula exhibits a permeability measurement of 33569± 344 mP.s at 6 rpm, whereas GOT4 demonstrates a permeability measurement of 54723± 380 mP.s at 6 rpm. During the skin irritation test, there was no apparent erythema and edema were observed when compared to the negative group. This may indicate that the designed microemulsion-based gel formulation demonstrates good biocompatibility with skin tissue. Topical delivery of vemurafenib is a promising route of drug administration to melanoma skin. Ionic liquids (ILs) have permeation-enhancing properties with either hydrophilic or lipophilic characteristics‎‎‎‎‎.